2019
DOI: 10.1039/c9ay00907h
|View full text |Cite
|
Sign up to set email alerts
|

Calibration strategies to correct for matrix effects in direct analysis of urine by ICP OES: internal standardization and multi-energy calibration

Abstract: Internal standardization and MEC can be used successfully to correct for matrix effects in direct analysis of urine by ICP OES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The results presented here were compared with those previously shown by Barros et al 9 for urine analysis using ICP-OES, considering the peculiarities of each instrumental method, as shown in Table 4. The operational conditions, for instance, were adjusted to provide the best results for the analytes in each method.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The results presented here were compared with those previously shown by Barros et al 9 for urine analysis using ICP-OES, considering the peculiarities of each instrumental method, as shown in Table 4. The operational conditions, for instance, were adjusted to provide the best results for the analytes in each method.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, despite the slopes being usually used as an indication of the occurrence of matrix effects, 9 the need to use internal standardization calibration as a correction strategy was evaluated based on the recovery results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High concentrations of EIEs and total dissolved solids can also cause severe matrix effects in elemental determination, impairing the reliability of the analysis. 50 Serrano et al 51 studied the effects of EIEs on MIP-OES signals and observed, for example, that Ca effects depend on the emission line evaluated. In general, signal enhancement was observed for atomic lines with a total energy ( E sum ) lower than 3.26 eV, while signal depression prevailed among atomic lines with E sum higher than 3.82 eV, as well as for all ionic lines evaluated.…”
Section: Performance and Limitations Of Mip-oesmentioning
confidence: 99%